ANCHOVY CORN COOKIES DENGAN SUBSTITUSI TEPUNG JAGUNG SEBAGAI PEMANFAATAN BAHAN PANGAN LOKAL - Endang Mulyatiningsih, Dwi Amrinaa Rosyadaa (Prosiding Pendidikan Teknik Boga Busana, 2020)
Kastangel is one of the most popular pastries in Indonesia. This pastry comes from the Netherlands, made from a mixture of flour, eggs, margarine and grated cheese. Rectangular with a length of about 3-4cm and a width of 1cm. The development of kastangel with the substitution of corn flour and anchovy additives as a substitute for cheese mixture can be used as an alternative to the use of local cereals as an innovation in the manufacture of pastry products. The nutritional value contained in corn and anchovy has a relatively low price which is expected to be able to meet the nutritional needs of the community. This study used the Research and Development method with 4-D capital, namely Define, design, develop, and dissemination and used a T-test to find out the community’s acceptance of Kastangel products with a substitution of 50% corn flour and anchovy additives. The proximate test results from the development of the Kastorn (Ancorn Cookies) product produce a nutritional value per 100g making this pastry more acceptable to the community. Keywords: Tepung jagung,Ancorn Cookies, Uji panelis, Uji proksimat